2020
DOI: 10.1002/nau.24370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of individual pelvic floor muscle training vs individual training progressing to group training vs group training alone in women with stress urinary incontinence: A randomized clinical trial

Abstract: Aims To assess the effects of individual pelvic floor muscle (PFM) training vs individual training (IT) progressing to group training (GT) vs group‐only training in women with stress urinary incontinence (SUI). Methods Randomized controlled and pragmatic clinical trials with 90 women with SUI. Participants were randomly allocated to one of three groups: IT, GT, or four individual sessions progressing to group training (IPGT). The intervention included 12 sessions, once a week, with direct supervision by a phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
2
3
0
1
Order By: Relevance
“…It is worth noting that other recent RCT supported the beneficial effect of pelvic floor muscle exercise combined with feedback in reducing incontinence severity based on Wexner FI SI [28,29] . In addition, biofeedback combined with pelvic floor exercises is better than pelvic exercises alone, for alleviating FI symptoms in nearly three forth of patients after12sessions of supervised training [30][31][32]. accordance with Lee and colleagues.…”
Section: Discussionsupporting
confidence: 56%
“…It is worth noting that other recent RCT supported the beneficial effect of pelvic floor muscle exercise combined with feedback in reducing incontinence severity based on Wexner FI SI [28,29] . In addition, biofeedback combined with pelvic floor exercises is better than pelvic exercises alone, for alleviating FI symptoms in nearly three forth of patients after12sessions of supervised training [30][31][32]. accordance with Lee and colleagues.…”
Section: Discussionsupporting
confidence: 56%
“…Similarly to our study, Sanchez et al [9] evaluated the responsiveness of the Spanish version of the PFIQ-7 after PFMT in women with PFM dysfunction (68.2 % of the women had UI, 27.1 % had prolapse and 29.4 % had anal incontinence) and found a moderate responsiveness. Besides, the primary outcome of RCT conducted and published previously [18] was related to urinary symptoms, fact that may be influenced the responsiveness of other subscales of both questionnaires that were not related to urinary symptoms. This is a limitation also commented by Barber et al [31] that reported a poor responsiveness of subscales of PFDI-20 and PFIQ-7 that were not related to the primary outcome evaluated in previous researchers conducted with another population.…”
Section: Discussionmentioning
confidence: 99%
“…This prospective observational study performed according STROBE checklist is secondary to a multicentre randomized clinical trial (RCT) that aimed to evaluate the effects of individual PFMT versus group PFMT for women with SUI. The RCT protocol and results of the study were previously published [17,18].…”
Section: Study Design and Enrollment Criteriamentioning
confidence: 99%
“…O treinamento auxilia na inibição do desejo, da sensação, ou urgência urinária. Além de melhorar a força da musculatura do assoalho pélvico, os exercícios desta musculatura incrementam a resistência e pressão de fechamento uretral, podendo ser realizados várias vezes ao dia 40,42,43 . Vale ressaltar que para a prática regular dos exercícios de modo ativo é necessário que a inervação dos músculos do assoalho pélvico esteja íntegra para a ativação do reflexo de Mahony.…”
Section: B Reeducação Vesical Ou Treinamento Vesicalunclassified